PERSPECTIVE OF JUNIOR RESIDENTS ON THE ROLE OF CHIEF RESIDENT AS A TEACHER IN OBSTETRICS AND GYNECOLOGY DEPARTMENT, UNIVERSITAS INDONESIA - WINARTO, HARIYONO; SETIAWAN, CAROLINE; ANGGRAENI, TRICIA D.; NURYANTO, KARTIWA H.; KUSUMA, FITRIYADI (International Journal of Applied Pharmaceutics, 2020)
Objective: Resident juniors are often exposed and taught by the Chief Residents in daily routines. However, there are no data regarding the quality of senior residents as teachers. We conducted a questionnaire-based evaluation to determine the quality of Chief Residents from a junior resident's perspective. Methods: This study was conducted from May to July 2019 in the Department of Obstetrics and Gynecology. Fifteen questions regarding the quality of chief residents as teachers, which consist of a safe learning environment, team working, coaching by demonstration and observation, stimulating learning and role modeling from junior’s perspective and one open question for suggestions were given using the Google Form internet-based application. Data were analyzed using Ms. Excel. Results: 75 junior residents (100%) participated in this study. Ten out of 15 questions were answered and agreed that the chief resident had qualifications as a teacher (88%). The most valued performances were the ability in selecting patients to the junior based on their level of competency and allowing them to do procedures (92%), while the most undervalued was chief resident’s ability to teach as good as their consultant (45%). Conclusion: Our study showed that most of the junior residents agreed that the presence of their senior is compulsory to their learning experience. Learning from seniors, including the consultant, will make a better learning environment.